Telexistence-based remote maintenance for marine engineers - Mazeas, Damien; Erkoyuncu, John Ahmet; Noël, Frédéric (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Remote work practice has seen significant developments in the field of maintenance, which is beneficial in the maritime sector. The defense industry is investigating the utilization of unmanned vehicle systems (UVS) to fulfil the demands of efficiency, safety, and field tasks that heavily rely on equipment usage. Telexistence technology affords marine engineers the capability to conduct inspections and repairs as if physically present. This study presents a scalable framework for evaluating the feasibility of conducting traditional machinery space maintenance through the implementation of telexistence capabilities. Our case study employs a physical robot for real-motion behaviors and a simulated virtual environment. Maintenance scenarios were developed through responses to a contextual questionnaire by two experts. In future steps, the study will compare telexistence with direct teleoperation in terms of presence, workload, and usability for vessel machinery space maintenance.
Keywords: virtual reality; remote control; human-robot interaction; telexistence; maintenance